Business Class travel preserves sleep quality and quantity and minimizes jet lag during the ICC women`s T20 world cup - Lalor, B. J.; Tran, J.; Halson, S. L.; Kemp, J. G.; Cormack, S. J. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To determine the impact of the quality and quantity of sleep during an international flight on subsequent objective sleep characteristics, training and match-day load, self-reported well-being, and perceptions of jet lag of elite female cricketers during an International Cricket Council Women`s T20 World Cup.